P1.10 Oral fluid based rapid syphilis testing. (8th July 2017) - Shannon, Chelsea; Bristow, CC; Cortina, SM Herbst De; Chang, JJ; Klausner, JD
Abstract : Introduction: Point-of-care syphilis testing currently uses fingerstick blood to identify Treponema pallidum (TP) antibodies by qualitative immunoassay. However, oral fluid testing is highly preferred by patients. We aimed to determine if rapid tests intended for whole blood could be used to detect treponemal antibody in oral fluid. Methods: Oral fluid was collected at the UCLA Care Clinic from 49 participants using Oasis SuperSAL (Vancouver, WA). The device uses an absorbent cylindrical pad to collect and filter ~1 mL of oral fluid. Oral fluid filtrate was evaluated with 3 rapid syphilis tests: SD Bioline Syphilis 3.0 (SD), MedMira Reveal TP (MM), and First Response Anti-TP (FR) following manufacturer directions for whole blood. Reference test results, TP particle agglutination (TPPA) and rapid plasma reagin (RPR), were extracted from participants' medical records. We used 3 different definitions as a reference standard. Definition 1: TPPA reactive. Definition 2: TPPA and RPR reactive. Definition 3: TPPA reactive and RPR titer >1:4. Specimens nonreactive on both the TPPA and RPR were considered negative. We calculated specificity and sensitivity for each definition, and used the exact binomial method to determine 95% confidence intervals (CI). Results: With definitions 1, 2 and 3 respectively, SD sensitivity was 86.4% (CI: 65.1, 97.1), 93% (CI: 66.1, 99.8), 100% (CI: 59.0, 100); MM sensitivity was 6.3% (CI: 0.2, 30.2), 9.1% (CI: 0.2, 41.2), 16.7% (CI: 0.4, 64.1); and FR sensitivity was 25% (CI: 8.7, 49.1), 25% (CI: 5.5, 57.2), 14.3% (CI: 0.4, 57.9). SD specificity was 56% (CI: 36.5, 75.5), MM specificity was 100% (CI: 35.9, 99.6) and FR specificity was 100% (CI: 83.9, 100). Conclusion: The high sensitivity of the SD test suggests a strong potential for oral fluid-based rapid syphilis testing. SD sensitivity increased with RPR titer. False positive results may be associated with the presence of non-venereal treponemal antibodies in oral fluid. The MM and FR tests had low sensitivity, perhaps due to differences in treponemal targets. Further research and development are needed.